2018
DOI: 10.1177/0956797617753606
|View full text |Cite
|
Sign up to set email alerts
|

Religious People Are Trusted Because They Are Viewed as Slow Life-History Strategists

Abstract: Religious people are more trusted than nonreligious people. Although most theorists attribute these perceptions to the beliefs of religious targets, religious individuals also differ in behavioral ways that might cue trust. We examined whether perceivers might trust religious targets more because they heuristically associate religion with slow life-history strategies. In three experiments, we found that religious targets are viewed as slow life-history strategists and that these findings are not the result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 36 publications
(60 reference statements)
5
47
0
Order By: Relevance
“…Life-history theory posits that organisms with slow life-history strategies exhibit traits and behaviors that are adapted to predictable and stable environments (Stearns, 1992). Recently, it has been proposed that atheists are seen as less trustworthy because, compared to religious people, they are not viewed as slow life-history strategists (Moon, Krems, & Cohen, 2018). It has been suggested that atheists are associated with fast life-history strategies that represent ecological unpredictability and uncertainty (Moon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Life-history theory posits that organisms with slow life-history strategies exhibit traits and behaviors that are adapted to predictable and stable environments (Stearns, 1992). Recently, it has been proposed that atheists are seen as less trustworthy because, compared to religious people, they are not viewed as slow life-history strategists (Moon, Krems, & Cohen, 2018). It has been suggested that atheists are associated with fast life-history strategies that represent ecological unpredictability and uncertainty (Moon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is interesting given different affective responses among religious groups (Gallup, ; Pew Research Center, ) as well as prior research showing that religious cue usage in marketing communications generally increases product evaluations (Dotson & Hyatt, ; Minton, ; Taylor et al, ). These findings are particularly interesting in that they also contradict a large body of prior research showing a positive halo effect of religion on evaluations of people (c.f., Bailey & Vietor, ; Bailey & Young, ; Isaac, Bailey, & Isaac, ) as well as greater trust of religious people (c.f., Gervais, Shariff, & Norenzayan, ; McCullough, Swartwout, Shaver, Carter, & Sosis, ; Moon, Krems, & Cohen, ). Put simply, results from the studies herein suggest that religious cues do not have the same effect for products as they do for people.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these observations, religions' adherents tend to be viewed as trustworthy (Hall, Cohen, Meyer, Varley, & Brewer, 2015;McCullough, Swartwout, Shaver, Carter, & Sosis, 2016;Tan & Vogel, 2008) and this trustworthiness is linked to perceived reproductive strategies (Moon, Krems, & Cohen, 2018;Moon et al, 2019). That is, people tend to trust religious targets more than nonreligious targets because of their supposed adherence to long-term mating strategies, including more restricted sexual orientations and reduced sexual promiscuity, male abandonment, and female cuckoldry.…”
mentioning
confidence: 73%